Cognitive complaints in breast cancer patients treated with chemotherapy: a reality? - Lange, Marie; Joly, Florence (Translational Cancer Research, 2017)
Memory and attention dysfunction is a common complaint among cancer survivors, named “chemobrain”, which can be reported during and even several years after treatment. These disorders have a negative impact on patients’ quality of life (1) and can disturb ability to work (2). Recent studies assessed self-reported cognitive function in cancer patient cohorts, mainly in breast cancer women, and showed that 46% to 60% of survivors had cognitive complaints (3-5). However, these studies did not use a validated questionnaire specifically constructed to assess cognitive complaints.